PENGARUH INOVASI PRODUK, HARGA DAN CITRA MERK TERHADAP KEPUTUSAN PEMBELIAN MOBIL BEKAS (STUDI KASUS SHOWROOM THE KING COBRA AUTO JAKARTA TIMUR) - Burhan Murdani (Fakultas Ekonomi dan Bisnis (FEB) Universitas Labuhanbatu, 2023)
The purpose of this study is to prove product innovation, price and product quality influence used car purchasing decisions at The King Cobra Auto Showroom, East Jakarta. This research is included in the survey research method, so this research design is quantitative descriptive research. The population referred to in this study is the population of sales data owned by Showroom The King Cobra Auto East Jakarta for the period June 2022 to March 2023. While the sample is important parts of the population on condition that they have experience and have transacted at The King Cobra Auto Showroom, East Jakarta so that this sampling technique includes purposive sampling with a total of 50 respondents. In research is positive so that it uses a Likert scale and analysis techniques in research using SmartPLS using the outer model and inner model approaches. The results showed that used car product innovation did not affect purchasing decisions. On the other hand, the price and brand image of used cars are still considered by consumers in this study in deciding to buy a used car.